Polycystic Ovary Syndrome - An Opportunity To Practice Proactive Preventive Medicine - Prasad , Indrajit (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Abstract not available J Bangladesh Coll Phys Surg 2021; 39: 209-210